'We go for a homely feel … not the clinical dementia side': care home managers' experiences of supporting residents with dementia to orientate and navigate care environments. Issue 7 (14th July 2022) - Heward, Michelle; Adams, Amanda; Hicks, Ben; Wiener, Jan
Abstract: Living with dementia can adversely affect people's spatial (orientation and navigation) and reality (time, date and place) orientation, which can detrimentally impact on their sense of social inclusion and wellbeing. This is an important challenge to address within United Kingdom (UK) care homes where around 70 per cent of the residents are living with dementia or severe memory problems. Care home managers have some autonomy in decision-making that impacts on the daily functioning of residents and are key in enacting the orientation and navigation agenda within a care home environment. Yet a paucity of literature explores their understanding and experiences of this issue. Contributing to this knowledge gap, our exploratory study examined managers' current practice of supporting residents with dementia to minimise disorientation and their knowledge of dementia-friendly design principles, guidelines and audit tools. Semi-structured telephone interviews with 12 UK care home managers were conducted. Questions started generally targeting residents' orientation and navigation abilities, followed by specific questions to draw out strategies used to support residents. Thematic analysis identified three higher-order themes: aligning strategies with needs, intuitive learning and managing within the wider business context. The findings demonstrated that managers perceive dementia to impact on a person's spatial and reality orientation. Consequently, the strategies they chose to adopt were tailored towards alleviating both challenges. However, although managers were aware of some design principles, they frequently relied on intuitive learning and past experiences to inform their choice of interventions, reporting a lack of knowledge and/or time to seek out orientation-specific training and guidance, resulting in a low uptake of guidelines and audit tools in practice. This gap between theory and practice highlights a need for accessible guidelines that integrate strategies with neuropsychological theory, and appropriate training to improve orientation and navigation in care home environments. Managers, staff, business owners, architects and designers all play a key role in implementing orientation guidelines into practice and ensuring dementia-friendly care home environments for residents.